PENGARUH KEAKTIFAN SISWA DALAM KEGIATAN EKSTRAKURIKULER TERHADAP PRESTASI BELAJAR SISWA DI SMP - Novianti Rahmawati; M. Qahfi; Ardian Mariyanto (STKIP MUHAMMADIYAH SAMPIT, 2019)
The research is an effort to know of Influence of Student Activity in Extracurricular Activity to Student Achievement of Class VIII SMP Negeri 8 Sampit Lesson Year 2017/2018. The study used a quantitative approach. The population in this study are all students of class VIII In SMP Negeri 8 Sampit Lesson Year 2017/2018 which amounted to 100 students. The technique used in sample collection is a saturated sampling technique, then the sample size is 100 students. Data collection techniques used questionnaires and documentation. Calculation of hypothesis testing using simple linear regression, before the analysis test is done the prerequisite test is the normality test, linearity test and autocorrelation test. Hypothesis testing obtained results that indicate that there is influence of student activity in student extracurricultural achievement to student learning achievement. Shown by thitung result ≥ ttable (2,733> 1,660) and sig